Zespół antyfosfolipidowy a zmiany w narządzie wzroku - Gerkowicz, Marek; Latalska, Małgorzata; Kosior-Jarecka, Ewa; Kozioł-Montewka, Maria; Pietraś-Trzpiel, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Antiphospholipid syndrome (APS) is one of the most often secondary trombophilic state, characterized by recurrent arterial and venous thrombosis, recurrent pregnancy loss, and the presence of circulating antiphospholipid antibodies. Ophthalmologic features are present in 15-88% of the patient with primary APS. In this article pathogenesis and clinical picture, especially ocular complications are presented.